Scripts : elegant lettering from design's Golden age - Heller, Steven (New York, NY : Thames & Hudson, 2011)
- Introduction##- French scripts##- British scripts##- German der schrift##- Italian il corsivo##- American scripts##- Further reading. ## ##Scripts never go out of style, and the hundreds of inventive examples here – many found in obscure sources from across Europe and America – are sure to inspire today's designers.##Derived from handwriting, these are typefaces that are stylized to suggest, imply or symbolize certain traits linked to writing.##From wedding invitations to advertisements, from menus and street signs to diplomas, script typefaces lend elegance and sophistication to a wide range of designs.##Drawn from the Golden Age of scripts, from the 19th to the mid-20th century, this collection will be an invaluable sourcebook for anyone with an interest in graphic design or typography.
boek